LIMITED ENDOSCOPIC SEPTAL SURGERY (LESS) - PILOT STUDY OF A NOVEL TECHNIQUE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Septoplasty is a commonly performed procedure in otorhinolaryngology. Septoplasty can be performed by the traditional trans nasal trans speculum (TNTS) technique or endoscopically. Limited Endoscopic Septal Surgery (LESS) is a further evolution of endoscopic septoplasty, where the dissection is limited to the area of deviation/ spur. Such limited dissection minimizes complications. This study was conducted to evaluate this novel technique. Objective: To compare the pre and postoperative quality of life of patients undergoing limited endoscopic septal surgery using a subjective questionnaire. Methods: This is a pilot study. 76 symptomatic patients with nasal septal deviation were selected during the period November 2021 to May 2023. Preoperative symptom score was assessed using Nasal Obstruction Symptom Evaluation questionnaire (NOSE) and was recorded. All patients underwent the surgery and were discharged as per institutional protocol. Each patient was called for follow-up after a week and were examined endoscopically. They were called for a second follow up after three months. Postoperative scoring was done at this point. Results: The mean preoperative NOSE score was 67±17 SD out of 100. Three months postoperatively this decreased to 30±16 SD. This was statistically significant. Our complication rate was 3%. Conclusion: Limited endoscopic septal surgery reduces complications and shortens the time for healing - we were able to discharge all our patients on the second postoperative day and only one patient had intra and postoperative complications.